PRIMARY EDUCATION AND SOCIAL ISSUES IN SOCIETY: HOW THE FUTURE OF CHILDREN NEEDED EDUCATION - Sarvinoz Tursunova; Nigina Muhammadova (Web of Journals Publishing, 2024)
Elementary education is one of the most important stages in a child's life. During this period, a fundamental approach to children's learning is formed, and a foundation is laid for them to become active and responsible members of society in the future. In this regard, primary education has a direct impact on the overall development of society, the solution of social problems, and in particular, on the future successful life of children.
Keywords: Problem, solution, future, primary education, social murder, economic murder, creativity.